2010
DOI: 10.1590/s0104-11692010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pattern of Risky Behaviors for Reproductive and Sexual Health Among Middle- and High-School Students

Abstract: This research aimed to establish the prevalence and factors associated with the pattern of risky behavior for reproductive and sexual health (PRBRSH) among secondary education students in Santa Marta, Colombia. A cross-sectional study was done. The PRBRSH was defined as having had two or more out of four possible risky sexual practices across the lifetime. Logistic regression was calculated to control for confounding variables. In total, 804 students reported lifetime sexual intercourse. PRBRSH was reported by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
3
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 9 publications
2
14
3
5
Order By: Relevance
“…For example, risky sexual behaviors (such as multiple sexual partners and unprotect sexual intercourse) among adolescents and youths have been shown to be easy to co-occur with a range of other risky behaviors including alcohol drinking, cigarette smoking, drug use, and violence [1,2,6-8]. In turn, substance use and violence have been implicated in increasing the likelihood for participation in risky sexual behaviors [1,5-7]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, risky sexual behaviors (such as multiple sexual partners and unprotect sexual intercourse) among adolescents and youths have been shown to be easy to co-occur with a range of other risky behaviors including alcohol drinking, cigarette smoking, drug use, and violence [1,2,6-8]. In turn, substance use and violence have been implicated in increasing the likelihood for participation in risky sexual behaviors [1,5-7]. …”
Section: Introductionmentioning
confidence: 99%
“…Researches in other countries similarly found a higher prevalence of risky sexual behaviors and substance use in adolescents and youths [5,7-9]. Given the higher prevalence of risky sexual behaviors and substance use, adolescents and youths aged 15 to 24 years represent approximately 25% of sexually active persons and account for nearly half of new HIV infection each year in the USA [10].…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on the mother, whose bond with the adolescent and decision-power Current Brazilian and international studies published in this periodical and that promote interfacing with the theme addressed in this study show scientific evidence focused on the social aspects concerning vulnerability that pervades adolescence, especially highlighting the use of drugs (11)(12) , domestic violence (13) , and sexual and reproductive health (6) .…”
Section: Data Concerning Adolescent Pregnancy In Latinmentioning
confidence: 96%
“…A study conducted in Colombia with 3,575 adolescents concluded that approximately one in each three participants presented risky sexual and/ or reproductive behaviors, including experiencing an unplanned pregnancy (6) . An unplanned pregnancy that is also an unwanted pregnancy may pose a severe problem for the sexual and reproductive health of adolescents and young individuals, as assistance required due to abortions show (7) .…”
Section: Data Concerning Adolescent Pregnancy In Latinmentioning
confidence: 99%
“…Also, de Walque (2006) finds that education is an important predictor of sexual behaviors in Burkina Faso, Cameroon, Ghana, Kenya, and Tanzania. In the case of Colombia, Varela et al (2011) estimate the prevalence of risky sexual behaviors and analyze their relationship with socio-demographic characteristics in adult population from all regions of the country; Campo-Arias et al (2010) study the prevalence and factors related with risky behaviors for reproductive and sexual health for high school students in the city of Santa Marta, and Brook et al (2002) identify the relationships between drug use, risky sexual behaviors and early pregnancy in Colombian teenagers.…”
Section: Introductionmentioning
confidence: 99%